2020
DOI: 10.1111/pirs.12523
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pedestrian crashes using a spatial count data model

Abstract: We develop a methodology to analyze pedestrian crash frequency in relation to neighborhood characteristics and exposure to traffic using a spatial count data model with a Poisson framework that is expanded to consider spatial factors, a methodological innovation. We also develop and apply a methodology for defining urban boundaries in mid‐sized metropolitan areas, following the functionality of the urban area. These methodologies are applied to a case study. The case study identifies specific neighborhood soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Built environmental factors at regional level [ 27 ] include also neighborhood design and land use and socioeconomic features of the districts where the elderly pedestrians live. Many authors have studied the relationship between pedestrian collisions and macrolevel built environmental factors [ 42 , 43 , 44 , 45 ]. Wedagama et al [ 42 ] found that pedestrian casualties in the city center zone are particularly associated with an increase in retail and community land use during working hours.…”
Section: State Of the Art On Road Safety Of Pedestrians And Elderly P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Built environmental factors at regional level [ 27 ] include also neighborhood design and land use and socioeconomic features of the districts where the elderly pedestrians live. Many authors have studied the relationship between pedestrian collisions and macrolevel built environmental factors [ 42 , 43 , 44 , 45 ]. Wedagama et al [ 42 ] found that pedestrian casualties in the city center zone are particularly associated with an increase in retail and community land use during working hours.…”
Section: State Of the Art On Road Safety Of Pedestrians And Elderly P...mentioning
confidence: 99%
“…Some authors have even demonstrated that some built environmental factors contribute to pedestrian collisions more than road infrastructure conditions do. Apardian and Smirnov [ 45 ] found that socioeconomic neighborhood features are more significant to predict the occurrence of pedestrian collisions than is traffic exposure, measured in Vehicles Miles Travelled (VMT). Furthermore, they suggested that a proper policy to improve road safety in urban areas would be periodic renovation and building of easy-to-adapt environments, because traffic volume or land use changes may deteriorate the road safety of a certain territory.…”
Section: State Of the Art On Road Safety Of Pedestrians And Elderly P...mentioning
confidence: 99%
“…Pedestrians in low-income communities are more expected to be damaged in accidents due to the absence of safe infrastructure. Suburban neighbourhoods are sometimes deemed undesirable for walkers, despite the fact that wealthy regions may have well-organized roadways, traffic signals, and pedestrian facilities ( Apardian & Smirnov, 2020 ; Lee et al, 2020 ; Qiao et al, 2020 ). People who live in affluent areas are often thought to be more cautious and drive safer cars.…”
Section: Introductionmentioning
confidence: 99%
“…People who live in affluent areas are often thought to be more cautious and drive safer cars. Because they can't afford a car, residents of low-income areas are more vulnerable against car crashes because they have no choice but to walk ( Apardian & Smirnov, 2020 ).…”
Section: Introductionmentioning
confidence: 99%